1946
DOI: 10.1021/ja01209a041
|View full text |Cite
|
Sign up to set email alerts
|

Complex Formation with High Molecular Weight Amines. II.1 A Spectrophotometric Study of the Dodecylamine—Cupric Acetate System

Abstract: In the first paper,3 it was mentioned that no complex compounds of high molecular weight amines and metal salts containing a ratio of amine to metal greater than 2:1 could be obtained. However, it has been noted that a solution of a 2:1 complex containing copper becomes a deeper blue upon the addition of an excess of the corresponding amine. With the thought that compounds other than the 2:1 complex might exist in solution, we have here attempted to apply the Method of Continuous Variations as expanded by Vosb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1947
1947
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…From the experimental result that the crystal phase did not change in the absence of OAm, we propose that the distributions of cation and anion were slightly rearranged after the removal of copper atoms/ions by OAm at high temperature (140 ° C) (Figure d). Copper ions/atoms are easily removed from the Cu 2 S lattice by amine molecules through the formation of copper–amine complexes. , Indeed, we observed the absorption peak assigned to the copper–amine complexes after the treatment of Cu 31 S 16 NPs with excess OAm (Figure e). The phase conversion is accompanied by a drastical change of LSPR peak (Figure f).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…From the experimental result that the crystal phase did not change in the absence of OAm, we propose that the distributions of cation and anion were slightly rearranged after the removal of copper atoms/ions by OAm at high temperature (140 ° C) (Figure d). Copper ions/atoms are easily removed from the Cu 2 S lattice by amine molecules through the formation of copper–amine complexes. , Indeed, we observed the absorption peak assigned to the copper–amine complexes after the treatment of Cu 31 S 16 NPs with excess OAm (Figure e). The phase conversion is accompanied by a drastical change of LSPR peak (Figure f).…”
Section: Resultsmentioning
confidence: 79%
“…Copper ions/atoms are easily removed from the Cu 2 S lattice by amine molecules through the formation of copper−amine complexes. 20,28 Indeed, we observed the absorption peak assigned to the copper−amine complexes after the treatment of Cu 31 S 16 NPs with excess OAm (Figure 4e). The phase conversion is accompanied by a drastical change of LSPR peak (Figure 4f).…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…This is believed to be due to the formation of a copper-oleylamine complex. 33,34 Likewise, these absorbance peaks were unaltered even when the solution was heated at 140 C (curve a). However, when hydroxyl ions are introduced, the peak around 630 nm subsided, whereas the peak at 350 nm, which is ascribed to CuO, remained 24 (curve b).…”
Section: Resultsmentioning
confidence: 96%
“…All these support the proposed formula with two stearate and two amine ligands within the coordination sphere. Broome et al reported bisdodecylamino–cupric acetate as an adduct of copper acetate and DDA. We have used [Cu­(St) 2 ], and the formation of bisdodecylamino–cupric stearate is responsible for selective removal process.…”
Section: Resultsmentioning
confidence: 99%
“…Here, the extraction capability of straight chain thiols and amines of variable chain length has also been demonstrated. Broome et al reported the binding of high molecular weight amine with metal complex in 2:1 fashion and again they studied dodecylamine–cupric acetate binding spectrophotometrically . We have introduced an interesting solid reagent greenish blue copper stearate (stearate is the higher homologue of acetate) to trap unbound straight chain amines leaving behind pure amine bound organosol intact.…”
Section: Introductionmentioning
confidence: 99%